Android-Based Digital Book Oriented to Multiple Chemical Representations on Terpenoid Learning Materials - Ummah, Nur Fadlilah Khoerul; Windayani, Neneng; Irwansyah, Ferli Septi; Sulaeman, Dedi (CV FOUNDAE, 2021)
This research aims to describe and analyze the application results of the developed digital book oriented to multiple chemical representations. The method employed in this research was the Design-Based Research (DBR) method with the ADDIE development model. The ADDIE development Model consisted of five stages to analyze, design, and develop a product. These stages covered the analysis of terpenoid material, the analysis of multiple representations of terpenoid material, and digital book design and development. The instrument used was a validation test questionnaire filled out by three validators. The result of this research is an Android-based digital book oriented to chemistry's multiple representations. The obtained robserved value was 0.83. Therefore, the developed digital book was declared valid and can be used as teaching material in the Natural Product Chemistry course.